ANTIBACTERIAL POTENTIAL TEST IN AGARWOOD (Gyrinops versteegii) STEM EXTRACT TOWARDS Escherichia coli and Staphylococcus aureus. - Mahdalena Sy Pakaya; Moh. Adam Mustapa; Muthiah Rahmah Ali (Jambura Journal of Health Sciences and Research, 2022)
Infection disease is one of the most common health problem in many developing countries, including Indonesia where the contamination of microbe is associated with the cause of the infection. The infection can be caused by various microorganisms such as bacteria, virus, fungus, and protozoa. Fortunately, Indonesia's medicinal plant varies and one of which is agarwood (Gyrinops versteegii). This study aims at measuring the potential of agarwood (Gyrinops versteegii) stem extract towards Escherichia coli and Staphylococcus aureus. In this study, the simplicial of agarwood stem is extracted by applying multilevel maceration method with n-Hexane solvent, ethyl acetate, and methanol. The result of antibacterial activity testing over three extracts reveals that the ethyl acetate extract can inhibit the growth of Escherichia coli dan Staphylococcus aureus. In addition, the result of screening in the ethyl acetate extract discovers that in contains alkaloid, terpenoid, and tannin, where the positive control used is chloramphenicol and the negative control is Dimethyl Sulfoxide (DMSO). The result of Minimum Inhibitory Concentration test in the agarwood stem extract towards Escherichia coli dan Staphylococcus aureus shows that the concentration of 50% is marked with absence of turbidity, whereas 50% in the Lowest Lethal Dose value signifies absence of growth in the bacteria in the Nutrient Agar (NA) media. Additionally, the result of potential test of agarwood stem ethyl acetate extract towards Escerichia coli in concentrations of 25%, 50%, and 100% with an inhibition zone created of 7,85 mm where it includes in medium category, and 10,6 mm and 13,45 mm that include in strong category. In the meantime, the result of potential test of agarwood stem ethyl acetate extract towards Staphylococcus aureus in concentrations of 25%, 50%, and 100% with an inhibition zone created of b,1 mm where it includes in medium category, and 13,2 mm and 16 mm that include in strong category in inhibiting bacteria.